Rare bird documentation form for Glaucous Gull at Lock and Dam 19 near Keokuk, 1985 - Cecil, Robert I.et al (1985)
Rare bird documentation form for two Glaucous Gulls at Lock and Dam 19 near Keokuk in Lee County, IA on January 13, 1985. Epson - sheet feed